Living alone reduces the decline of calf circumference among Chinese older adults: A 4-year longitudinal study - Wang, Dong; Zhang, Jun (Frontiers in Aging, 2022)
Background: Calf circumference (CC) is regarded as a surrogate marker of skeletal muscle mass with high sensitivity and specificity for predicting sarcopenia. A cross-sectional study reported older adults living alone were at high risk of developing sarcopenia. Whether living alone affects the change of CC is unknown and there is no evidence from longitudinal study. The purpose of this study was to investigate the relationship between living arrangements and the change of CCs among older adults in China. Methods: The data were from the Chinese Longitudinal Healthy Longevity Survey. A total of 2203 older adults (age ≥65 years, mean age: 80.61±8.30 years, 50.0% female) who were interviewed in 2014 and then 2018 follow-up survey were finally included for analysis. Living arrangements and other information were collected in 2014. CCs were measured and recorded in the questionnaires of two waves and the differences were calculated. Logistic regression analyses were conducted to evaluate the association of living arrangements (living alone or not living alone) with the change of CCs (decline or no decline). Results: There were 446 (20.2%) participants living alone and 1757 (79.8%) participants not living alone. After about four years, CCs of 866 (39.3%) older adults declined. Compared to not living alone, living alone was negatively associated with CC decline, even after adjustment for covariates (OR: 0.702, 95% CI: 0.547-0.901, P=0.005). This significant association was found in 65-79 years old (OR: 0.619, 95% CI: 0.407-0.942, P=0.025), female (OR: 0.567, 95% CI: 0.408-0.790, P=0.001) and city/town (OR: 0.461, 95% CI: 0.310-0.685, P<0.001) subgroups but not in advanced age (≥80 years old), male and rural subgroups. Conclusions: This study revealed that living alone was associated with a decreased risk of CC decline among older adults, and might be a protective factor for sarcopenia.